Do Local and International Shocks Matter in the Interconnectedness amid Exchange Rates and Energy Commodities? Insights into BRICS Economies - Qabhobho, Thobekile; Adam, Anokye M.; Asafo-Adjei, Emmanuel (International Journal of Energy Economics and Policy, 2023)
The study examined the interdependence structure among energy (brent, natural gas and petroleum) commodities returns, crude oil implied volatility, and exchange rate returns and volatilities in the context of BRICS across time and/or frequencies. The wavelet approaches (bi-wavelet, partial wavelet and wavelet multiple) were employed for the period from May 07, 2012, to March 31, 2021. It was revealed that co-movements between exchange rate returns and energy commodities were negative and significant at certain times and frequencies. In this case, causality emanated from exchange rate returns. Moreover, in most instances, implied volatilities strongly impacted the exchange rate and energy interconnectedness returns. We found strong integration levels among the financial time series with Petroleum having the most likelihood to lead or lag. Findings from the study imply that co-movements between exchange rate returns and energy commodities are heterogeneous and adaptive. Also, local shocks (exchange rate volatilities), have the greatest spillover effect between exchange rate returns and energy commodities relative to implied crude oil volatility. This is the first study that employs the wavelet approaches to investigate the conditional effects of local and external shock on the comovement between exchange rate returns and energy commodities’ returns.